Regional economic convergence in the euro area - Zeli, Alessandro; Truglia, Francesco (European Spatial Research and Policy, 2025)
The study of the convergence of the euro area (EA) regions allows to test theoretical hypotheses such as: the ex-post satisfaction of the OCA conditions and the resilience to the crisis of the OCA countries. Related to these facts, it has to be noted the emergence of new centers and peripheries in the European Union and euro area. We considered the per capita GDP over the period 2001–2018, the analysis is carried out by applying different methodologies such as: convergence indicators and spatial statistics models. Our results confirm the presence of divergent processes among the EA regions.